Museum Mulawarman sebagai Pusat Konservasi Warisan Budaya - Rae Larasati; Jamil Jamil; Marwiah Johansyah (Yupa: Historical Studies Journal, 2017)
The purpose of this paper is to determine the values of the Hindu-Buddhist culture, which is in the Museum of Mulawarman Tenggarong, Kutai Kartanegara Regency. Based on the findings and discussion shows that cultural values that are in the Museum of Mulawarman are religious, historical, cultural values and social values. The Government's efforts to preserve the cultural values of Hinduism-Buddhism is divided into three: protection, care, and adhering to the rules